The French Revolution and its legacy - Roman, Camil, author. Link
1 online resource (240 pages)
Keywords: This book offers an interpretation of the French Revolution and modern democracy, arguing that the revolution gave rise to a democratic power that is liminal by nature, and therefore unlimited, unaccountable on principle, and the basis for a state religion of continuous transformation. It demonstrates these claims by focusing on the universally adulated but little understood sacred motto 'liberté, egalité, fraternité', and on the sacrifice and role of Louis XVI in the revolution. Analysing the revolutionary process by which representative democratic government took the shape of political metamorphosis, the book shows that modern democracy does not represent the people but refers to the representation of representation and the existential condition of permanent displacement. The present study will appeal to scholars from across the social, political and human sciences with an interest in the French Revolution, modern democracy, political modernity, contemporary politics and the history of art.